Association between triglyceride‐glucose index and arterial stiffness reflected by carotid pulse‐wave velocity in stage 1 hypertension and individuals with normal/elevated blood pressure. Issue 2 (24th January 2023) - Wang, Yonghuai; Wang, Shan; Pan, Xiaofang; Meng, Pingping; Yang, Jun; Zhang, Yuhua; Liu, Minghui; Li, Mingxing; Gao, Jie; Wu, Qiang; Feng, Ningna; Wu, Yiyun; et al.
Abstract: Evidence of the triglyceride‐glucose (TyG) index as an independent predictor of arterial stiffness in stage 1 hypertension patients is scarce. This study aimed to explore the association between TyG index and arterial stiffness in this population. A total of 1041 individuals from 32 centers with normal/elevated blood pressure (BP, <130/80 mmHg; 345 men (33%); median age, 37 years) and 585 stage 1 hypertension patients (BP ≥130/80 and <140/90 mmHg; 305 men (52%); median age, 47 years) were prospectively enrolled. Arterial stiffness was determined by measuring carotid ultrafast pulse‐wave velocity (ufPWV). TyG index was calculated as ln (fasting triglyceride (TG) × fasting blood glucose/2). Patients with a higher TyG index tended to have higher ufPWV. The TyG index was positively associated with ufPWV at the end of systole in stage 1 hypertension patients after adjusting for confounding factors ( β for per unit .48), and restricted cubic spline analysis confirmed a linear association. Subgroup analyses in terms of age, sex, and body mass index yielded similar results. However, no significant relationship was observed between the TyG index and ufPWV in the population with normal/elevated BP. The fully adjusted β between ufPWV and the TyG index was higher than the TG/high‐density lipoprotein cholesterol ratio, TG, and pulse pressure. In conclusion, patients with a higher TyG index had greater arterial stiffness, and the TyG index independently and positively correlated with arterial stiffness in stage 1 hypertension patients. The TyG index may provide a simple and reliable marker to monitor arterial stiffness in hypertensive patients.